2020
DOI: 10.2147/ott.s240843
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Nomogram for Patients with Radical Surgery for Non-Metastatic Colorectal Cancer Incorporating Hematological Biomarkers and Clinical Characteristics</p>

Abstract: Background: There is a large difference in postoperative survival in patients with nonmetastatic colorectal cancer. We aimed to develop nomograms incorporating both hematological biomarkers and clinical characteristics to predict overall survival (OS) in patients with radical surgery for non-metastatic colorectal cancer. Methods: A retrospective analysis was performed on date from 508 patients who underwent radical resection of colorectal cancer at the Affiliated Tumor Hospital of Guangxi Medical University fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Finally, because there is no information on blood biomarkers such as serum lactate dehydrogenase (LDH), alkaline phosphatase, and carcinoembryonic antigen (CEA) in the SEER database, and thus these were not included in the analysis. Some previous studies have shown that combining blood biomarkers, such as hemoglobin, neutrophils, and LDH, can improve the predictive capability of the nomogram 24 . We will include these data in future research to improve the nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because there is no information on blood biomarkers such as serum lactate dehydrogenase (LDH), alkaline phosphatase, and carcinoembryonic antigen (CEA) in the SEER database, and thus these were not included in the analysis. Some previous studies have shown that combining blood biomarkers, such as hemoglobin, neutrophils, and LDH, can improve the predictive capability of the nomogram 24 . We will include these data in future research to improve the nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Next, our manuscript has not included other characteristics, such as hematological biomarkers and molecular parameters. As some studies suggested, combining some hematological biomarkers, such as HGB, neutrophils and LDH, can promote the predictive ability of a nomogram [31], while molecular parameters, including miRNA, CpG methylation and circular RNA, have been demonstrated to be useful for predicting the survival of patients [32][33][34]. Therefore, we will improve and perfect this work in our future study by combining these characteristics.…”
Section: Discussionmentioning
confidence: 94%
“…Nomograms had been regarded as efficient tools in clinical practice, which couldpredict numerical probabilities for individual patients by incorporating critical prognostic factors [ 30 ]. Many nomograms had demonstrated superiority over the traditional TNM staging system in predicting survival in multiple malignancies [ 31 – 34 ]. Several studies had constructed prognostic nomogram of patients with GSRC; however, these researches had either limited population selection or absence of accurate tumor location.…”
Section: Discussionmentioning
confidence: 99%